2006
DOI: 10.1017/s0025315406014020
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of the genus Elzalia (Nematoda: Monhysterida: Xyalidae) from the Yellow Sea, China

Abstract: Two new species of free-living marine nematodes of the genus Elzalia, Elzalia gerlachi sp. nov. and Elzalia striatitenuis sp. nov. from the Yellow Sea, China, are described and illustrated. Elzalia gerlachi sp. nov. is characterized by relatively large body length (1540–1740 μm in males; 1510–1780 μm in females), spicules 135–160 μm (3.33–3.90 anal body diameter) and complex gubernaculum. Elzalia striatitenuis sp. nov. is characterized by rather small body size (560–660 μm in males; 570–630 μm in females), sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Preferably they should also integrate different taxonomic methods (Fonseca et al , in press). There are numerous possibilities for identification tools used in nematology: dichotomous (Andrássy, 1981, 2006), polytomous (Decraemer & Gourbault, 2000; Lamberti et al , 2000), graphical polytomous (Fonseca et al , 2006a), pictorial (Platt, 1984; Decraemer et al , 1997; Tchesunov & Mokievsky, 2006), tabular (Fonseca et al , 2006b; Zhang & Zhang, 2006) and computer-assisted (Diederich et al , 2000). Recently, several authors have shown the importance of using statistics for species differentiation (Gozel et al , 2006; Derycke et al , 2008; Fonseca et al , in press).…”
Section: Discussionmentioning
confidence: 99%
“…Preferably they should also integrate different taxonomic methods (Fonseca et al , in press). There are numerous possibilities for identification tools used in nematology: dichotomous (Andrássy, 1981, 2006), polytomous (Decraemer & Gourbault, 2000; Lamberti et al , 2000), graphical polytomous (Fonseca et al , 2006a), pictorial (Platt, 1984; Decraemer et al , 1997; Tchesunov & Mokievsky, 2006), tabular (Fonseca et al , 2006b; Zhang & Zhang, 2006) and computer-assisted (Diederich et al , 2000). Recently, several authors have shown the importance of using statistics for species differentiation (Gozel et al , 2006; Derycke et al , 2008; Fonseca et al , in press).…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate that nematode diversity is high and most nematodes are rare species comprising only one or two individuals. Description of new nematode taxa is in progress but, because of taxonomic problems, the number of new species described from the seas of China so far represents only about 1/100 of known species in the world oceans (Tchesunov 2006;Zhang and Zhang 2006;Huang and Wu 2011;Huang and Xu 2013). In this paper we describe one new genus and two new species from the subtidal sediment in the East China Sea: Pseudelzalia longiseta gen. nov., sp.…”
Section: Introductionmentioning
confidence: 94%
“…In the past few years, in order to study the biodiversity of free-living marine nematodes in the Yellow Sea, China, sediment samples were collected in many sites from the intertidal to the sublittoral region of the Yellow Sea. A total of 223 species of nematodes, of which three new genera and 21 new species have been described were determined from these habitats (Huang & Zhang, 2004, 2005, 2006a, b, 2007; Zhang & Zhang, 2006). The present paper describes two new species which belong to the genera Daptonema Cobb, 1920 and Cobbia De Man, 1907 (Xyalidae).…”
Section: Introductionmentioning
confidence: 99%